Enhancing Ethnic Traditional Sports Education Through Sports Psychology: Significance, Challenges, and Strategies - Huang Y; Long B (Psychology Research and Behavior Management)
Yong Huang,1 Bang Long2 1Physical Education Institute, Hanjiang Normal University, Shiyan, Hubei, 442000, People’s Republic of China; 2Physical Education Institute, Hunan University of Science and Engineering, Yongzhou, Hunan, 425100, People’s Republic of ChinaCorrespondence: Bang Long, Email bcze042@163.comAbstract: As a vital carrier of Chinese national culture, ethnic traditional sports encapsulate the life wisdom and spiritual essence of diverse ethnic groups, serving as both intangible heritage and dynamic educational tools. While previous studies have addressed cultural preservation, this study innovatively integrates sports psychology theory with ethnic sports pedagogy, systematically examining how psychological principles—such as intrinsic motivation (Self-Determination Theory) and group dynamics—enhance students’ cultural identity, prosocial behaviors, and resilience. Through a mixed-methods approach combining literature analysis and cross-cultural case studies (eg, Japan’s kendo and Mexico’s ulama), we identify key barriers to implementation, including resource gaps and teacher training deficits, and propose actionable strategies: gamified curriculum design, AR/VR-enhanced cultural immersion, and community-driven psychosocial support systems. Our findings contribute to three domains: (1) a novel theoretical framework linking sports psychology to ethnic cultural education; (2) empirical evidence of stress inoculation techniques improving student persistence by 45%; and (3) policy recommendations for scalable, culturally adaptive teaching models. This work bridges the gap between tradition and modernity, offering a replicable blueprint for global educators seeking to harmonize cultural heritage with psychological pedagogy.Keywords: sports psychology perspective, ethnic traditional sports education, significance, limitations, optimization strategies